ABSTINENSI PADA MASA KEHAMILAN DALAM TRADISI MASYARAKAT DI DEMAK - Fuadah, Shofiatul; Ardinigsih, Zahra Zahara (JURNAL AL-AQIDAH, 2023)
This article reviews the epistemological study of taboos during pregnancy in Demak district. This research aims to construct Javanese society's knowledge regarding beliefs regarding taboos for pregnant women. Javanese people believe in this myth because of the tales of ancient people, and they are still believed in it today. This type of research includes qualitative research which explains Javanese people's beliefs in the myth of taboos for pregnant women. The data sources for this research are the results of interviews with pregnant women, community leaders, religious leaders, husbands and parents of pregnant women. The results of the research show that myths about taboos for pregnant women are still believed today by both young mothers and older people. Myths about taboos during pregnancy include the prohibition on eating pineapples, not being allowed to eat dempet bananas, dempet eggplants, eating dempet foods which have the meaning of not giving birth to conjoined twins, and not recommending eating spicy foods which are believed to prevent having angry children.